Birds of the Sun : Macaws and People in the U.S. Southwest and Mexican Northwest - Gilman, Patricia A.; Plog, Stephen; Schwartz, Christopher W., 1989- (Book collections on Project MUSE., 2022)
"The multiple, vivid colors of scarlet macaws and their ability to mimic human speech are key reasons they were and are significant to the Native peoples of the southwestern U.S. and northwest New Mexico. Although the birds' natural habitat is the tropical forests of Mexico and Central America, they were present at multiple archaeological sites in the region. Leading experts in southwestern archaeology explore the reasons why"--